Persepsi Masyarakat Terhadap Jasa Ekosistem Perkebunan Teh Medini, Kabupaten Kendal - Irda Mayasari; Mohammad Muktiali (Teknik PWK (Perencanaan Wilayah Kota), 2022)
This study discusses ecosystem services, which are natural resources that are utilized and managed by humans for their daily needs. This research was conducted at Medini Tea Plantation, Kendal Regency where there are plantation ecosystem services including artificial ecosystem services. However, at present the ecosystem services of Medini Tea Plantation have not been managed properly. This study aims to assess the community's perception of ecosystem services (providing, regulation and culture) at Medini Tea Plantation, Kendal. This study has 4 objectives, namely: (1) identifying the socio-economic characteristics of the respondents, (2) analyzing the community's perception of the provision of ecosystem services, (3) analyzing the assessment of the community's perception of the regulatory ecosystem service, (4) analyzing the perception of tourists/visitors on the cultural ecosystem services. The research approach was carried out quantitatively descriptive and qualitative with scoring analysis techniques. The research was conducted on 97 respondents from the Ngesrepbalong Village community and 35 respondents from visitors to the Medini Tea Plantation tourist attraction. The results of this study indicate that: (1) the average respondent works at the Medini Tea Plantation and is dominated by women who have lived since birth in Ngesrepbalong Village; (2) assessment of the perception of regulatory services in the medium category with a score of 1.73; (3) the assessment of the perception of regulatory services is in the high category with a score of 1.34; (4) the assessment of the perception of cultural services is in the high category with a value of 1.47.